2005
DOI: 10.1897/04-559r.1
|View full text |Cite
|
Sign up to set email alerts
|

Using aquatic macroinvertebrate species traits to build test batteries for sediment toxicity assessment: Accounting for the diversity of potential biological responses to toxicants

Abstract: An original species-selection method for the building of test batteries is presented. This method is based on the statistical analysis of the biological and ecological trait patterns of species. It has been applied to build a macroinvertebrate test battery for the assessment of sediment toxicity, which efficiently describes the diversity of benthic macroinvertebrate biological responses to toxicants in a large European lowland river. First, 109 potential representatives of benthic communities of European lowla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, several recent studies examined the trait responses of communities to various types of multiple (Statzner and Bêche, 2010) or single pressures, e.g. global warming (Bonada et al, 2007), exotic species proliferation (Statzner et al, 2008), eutrophication (Lecerf et al, 2006), salinity (Piscart et al, 2005(Piscart et al, , 2006, sediment toxicity (Ducrot et al, 2005), or river dynamics loss (Statzner et al, 2005).…”
Section: P2mentioning
confidence: 99%
“…However, several recent studies examined the trait responses of communities to various types of multiple (Statzner and Bêche, 2010) or single pressures, e.g. global warming (Bonada et al, 2007), exotic species proliferation (Statzner et al, 2008), eutrophication (Lecerf et al, 2006), salinity (Piscart et al, 2005(Piscart et al, , 2006, sediment toxicity (Ducrot et al, 2005), or river dynamics loss (Statzner et al, 2005).…”
Section: P2mentioning
confidence: 99%
“…In the second approach, the benthic indices recommended by the Assessment System for the Ecological Quality of Streams and Rivers throughout Europe using benthic macroinvertebrates ( [28]; www.aqem.de) were calculated. Third, the ecological traits defined by Usseglio-Polatera et al [29] and Ducrot et al [30] (Supplemental Data) were used to assess the colonization patterns and adjustment to dominant environmental characteristics at the Pallanza site.…”
Section: Sediment Sampling and Analysesmentioning
confidence: 99%
“…Fenoglio et al [43] demonstrated the importance of currents for the colonization process in lotic environments in North Italy. The data using the benthic macroinvertebrate ecological traits [29,30] were also analyzed. This showed that 71 to 86% of the taxa that colonized the experimental trays (which likely served as the hydraulic refugia for benthos) retrieved in April 2004 belong to F-group organisms (ecological preference for avoiding high current velocities) and to group 2 and 4 organisms (exhibit passive dispersal and live in the sections of the river with low flow).…”
Section: Colonization and Ni Bioavailabilitymentioning
confidence: 99%
“…In ecotoxicology, traits have also been used in some quantitative structure activity relationship (QSAR) models (Escher and Hermens 2004), the SPEAR index (Liess and Von Der Ohe 2005), in corrections of certain risk indicators for specific traits (e.g. lipid correction of bioconcentration factors), effect analysis and modelling using life table and life history traits (Arnot and Gobas 2004; Preuss et al 2009) and in test battery optimization (Ducrot et al 2005). However, it is rare that more than one or two traits are incorporated into these approaches, and the acquisition and use of traits has been made haphazardly, and thus the potential of traits for prospective environmental risk assessment remains to be fully explored (Baird et al 2008).…”
Section: Introductionmentioning
confidence: 99%